2019
DOI: 10.1098/rspb.2019.1498
|View full text |Cite
|
Sign up to set email alerts
|

Slow life-history strategies are associated with negligible actuarial senescence in western Palaearctic salamanders

Abstract: Actuarial senescence has been viewed for a long time as an inevitable and uniform process. However, the work on senescence has mainly focused on endotherms with deterministic growth and low regeneration capacity during the adult stage, leading to a strong taxonomic bias in the study of ageing. Recent studies have highlighted that senescence could indeed display highly variable trajectories that correlate with species life-history traits. Slow life histories and indeterminate growth seem to be associated with w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…included anurans and salamanders in their comparative analyses and found a great diversity in patterns of actuarial senescence among the four species that were studied. In contrast,Cayuela, Olgun, et al (2019) highlighted the absence of actuarial senescence in three species of salamanders from western…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…included anurans and salamanders in their comparative analyses and found a great diversity in patterns of actuarial senescence among the four species that were studied. In contrast,Cayuela, Olgun, et al (2019) highlighted the absence of actuarial senescence in three species of salamanders from western…”
mentioning
confidence: 95%
“…Although a few case studies on free-ranging populations failed to detect any increase in mortality rate with age (Cayuela, Olgun, et al, 2019;Jones et al, 2014), most recent syntheses revealed two major facts. First, actuarial senescence is a nearly ubiquitous process in the living world (Nussey, Froy, Lemaitre, Gaillard, & Austad, 2013;Shefferson, Jones, & Salguero-Gómez, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the underlying basis of their exceptional longevity remains unknown, salamanders exhibit an uncommon resistance to ageing. Although few studies have addressed this topic, these, together with evidence from captive records in zoos and laboratories, suggest that a number of urodele species do not display the traditional signs of physiological decay that accompany mammalian ageing and are thus considered organisms of "negligible senescence" (Finch, 1990;Margotta et al, 2002;Cayuela et al, 2019). This phenomenon, also observed in other vertebrates such as turtles, rockfish and naked mole rats (Finch, 2009), is intrinsically linked to a defiance of the Gompertz-Makeham law of mortality (Gompertz, 1825;Makeham, 1860), which states that death risk increases exponentially as an organism ages.…”
Section: Negligible Senescencementioning
confidence: 99%
“…This phenomenon, also observed in other vertebrates such as turtles, rockfish and naked mole rats ( Finch, 2009 ), is intrinsically linked to a defiance of the Gompertz-Makeham law of mortality ( Gompertz, 1825 ; Makeham, 1860 ), which states that death risk increases exponentially as an organism ages. Indeed, a recent study involving three salamander species ( Lyciasalamandra fazilae, Salamandra salamandra , and Salamandra perspicillata ), indicates that their mortality rate is stable and weakly affected by age, in keeping with them exhibiting negligible senescence ( Cayuela et al, 2019 ). This observation raises several important yet outstanding questions, including whether salamanders manifest cellular hallmarks of ageing as defined in mammalian contexts ( Lopez-Otin et al, 2013 ), whether they age at the molecular level, what principles govern ageing—or lack of — in these organisms and, in particular, what is the role played by their extreme regenerative abilities in this process.…”
Section: Negligible Senescencementioning
confidence: 99%